Mechanisms for Combating Crimes of Government Contract Tendering (A Comparative Study) - Mohammed Jassim, Researcher. Shaymaa; Hanoon Khaiaf, Prof. Dr. Ghazi (Basra studies journal, 2024)
Government contracts are a vital tool for the state in implementing its developmental and investment policies, directly linking them to public funds. The process of government contracting involves allocating significant financial appropriations, represented by large sums of public money. Due to the importance of these funds and their vulnerability to abuse by individuals, it is necessary to have a criminal confrontation to ensure the integrity of contracting procedures, preventing manipulation or tampering for the benefit of specific entities or individuals. Public officials, during the conclusion of these government tenders and auctions, may exploit their positions to serve personal interests by engaging in criminal acts known as corruption crimes and abuse of public office. This confrontation involves criminalizing actions and behaviors detrimental to the integrity of government tenders, as they are a fundamental tool used by administrations to execute government projects related to public facilities and their management. Additionally, mechanisms have been established to combat these crimes proactively, activating the role of supervisory authorities such as the public prosecution and the integrity commission. National and comparative legislations, as well as regional and international agreements, have undertaken the task of regulating mechanisms to combat crimes related to government contracts and criminalizing actions detrimental to them, whether in criminal laws or specialized laws regulating government contract tenders, or even the entities responsible for investigation and supervision, such as the Integrity Commission Law, Unlawful Gain Law, and other relevant laws. This is aimed at preventing crimes, corruption cases, and abuse of public office, which have a negative impact on government institutions and result in the waste of public funds.